Knowledge Of Patient’s Family About The Implementation of Triage In The Emergency Department - Idzni Nelia Mustafa; Wan Nishfa Dewi; Veny Elita (Media Keperawatan Indonesia, 2022)
Triage is the process by which patients are classified according to the type and urgency of their conditions to get help from a care provider. Patients and the patient families must know about the triage implementation to avoid misinterpretation of health services in the emergency unit. This study aims to identify the knowledge of patients’ families about the implementation of triage in the emergency department. The design of the study was quantitative with a cross-sectional technique. The sample of this study was the patient’s families with 90 people which were selected through accidental sampling. Data collection used was a questionnaire that has been tested for its validation and reliability. Data collected were analyzed using descriptive analysis. The majority of respondents had sufficient knowledge about triage 62,2%, the respondents accounted with better knowledge about triage was 22,2% and the respondents with a lack of knowledge 15,6%. It is be concluded that based on the result of this study, it is beneficial for health care professionals to provide triage education to patient’s families to improve patients' families' understanding of triage implementation in the emergency setting in the hospital